1997
DOI: 10.1007/bf01213306
|View full text |Cite
|
Sign up to set email alerts
|

Double cancers of the gallbladder and bile duct associated with anomalous choledochopancreatic duct junction

Abstract: A rare case of double cancers of the gallbladder and bile duct associated with anomalous choledochopancreatic duct junction (ACPDJ) is reported. The patient was a 61-year-old Japanese woman who with presented right upper quadrant abdominal pain. Liver function tests results were normal. Computed tomography showed a polypoid lesion in the gallbladder, and endoscopic retrograde cholangiopancreatography (ERCP) demonstrated ACPDJ and irregular wall of the inferior bile duct. A diagnosis of double cancers of the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21][22] (Note that the form of choledochal dilatation shown in Table 1 is according to Todani et al 23 ). The present patient represents the first reported case of triple carcinomas of the biliary tract, including lesions in the bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] (Note that the form of choledochal dilatation shown in Table 1 is according to Todani et al 23 ). The present patient represents the first reported case of triple carcinomas of the biliary tract, including lesions in the bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Tokiwa et al demonstrated that epithelial hyperplasia of the gallbladder was observed in children with anomalous arrangement of the pancreaticobiliary duct, implicating this condition in the carcinogenesis of these patients. Table 1 summarizes the 17 previously reported cases of double cancer of the biliary tract associated with PBM, based on MEDLINE search results between 1984 and 2004 . The gallbladder and the bile duct were the most common sites of double cancer reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the 17 previously reported cases of double cancer of the biliary tract associated with PBM, based on MEDLINE search results between 1984 and 2004. [14][15][16] The gallbladder and the bile duct were the most common sites of double cancer reported in the literature. Also, Uetsuji et al 17 note the significance of a low junction of the cystic duct (LJCD) as another anatomical variation which may have an association with biliary tract neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…inflammatory, malignant, or obstructive. 1,2 We report a case of spontaneous urinary ascites after upper abdominal surgery.…”
Section: Case Reportmentioning
confidence: 98%
“…Synchronous or metachronous cancers in the biliary system are often attributed to an abnormal pancreaticobiliary junction (APBJ), as a result of persistent reflux of pancreatic juice with subsequent biliary inflammation. [1][2][3][4] However, it is very rare for gallbladder and pancreatic neoplasms to co-exist; in fact, only three previous reports mention this association. [5][6][7] We report a case of a young woman with synchronous cancers in the gallbladder and pancreas.…”
Section: Introductionmentioning
confidence: 99%